2010
DOI: 10.1007/s10517-010-0972-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphofunctional Analysis of Experimental Model of Esophageal Achalasia in Rats

Abstract: We carried out a detailed analysis of rat model of esophageal achalasia previously developed by us. Manifest morphological and functional disorders were observed in experimental achalasia: hyperplasia of the squamous epithelium, reduced number of nerve fibers, excessive growth of fibrous connective tissue in the esophageal wall, high contractile activity of the lower esophageal sphincter, and reduced motility of the longitudinal muscle layer. Changes in rat esophagus observed in experimental achalasia largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Another achalasia model consists of local pharmacological denervation of the abdominal portion of the esophagus by wrapping the esophagus of albino rats with thick gauze soaked in the neurotoxin benzalkonium chloride. Apparent morphological and functional disorders were observed in the esophagus of this experimental achalasia model, correlating with changes in observed humans with achalasia [28,29]; another model involves the injection of benzyldimethyltetradecylammonium chloride into the distal esophagus of opossums to increase pressure in the lower esophageal sphincter; some of the histological observations resulting from this treatment resemble features of achalasia [30,31]. Furthermore, a report has shown that aged Rassf1a-deficient mice are more susceptible to megaesophagus than their wild-type littermates.…”
Section: Discussionsupporting
confidence: 55%
“…Another achalasia model consists of local pharmacological denervation of the abdominal portion of the esophagus by wrapping the esophagus of albino rats with thick gauze soaked in the neurotoxin benzalkonium chloride. Apparent morphological and functional disorders were observed in the esophagus of this experimental achalasia model, correlating with changes in observed humans with achalasia [28,29]; another model involves the injection of benzyldimethyltetradecylammonium chloride into the distal esophagus of opossums to increase pressure in the lower esophageal sphincter; some of the histological observations resulting from this treatment resemble features of achalasia [30,31]. Furthermore, a report has shown that aged Rassf1a-deficient mice are more susceptible to megaesophagus than their wild-type littermates.…”
Section: Discussionsupporting
confidence: 55%
“…The rat model of achalasia was successfully produced by injecting 0.2% BAC into the abdominal portion of the esophagus for ablation of the ganglion cells of the myenteric plexus. 33 Pathological changes were observed mainly in the middle and lower thirds of the esophagus, resulting in reductions in body weight and food intake, malnutrition and immune impairment. The animal model set up and treatment plan are summarized in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…4,28,48,68,69,73,79,88 Using gauze soaked with benzalkonium chloride (BAC) wrapped around the abdominal portion of the esophagus in rats, investigators demonstrated that the esophageal diameter was increased and the number of myenteric plexus neurons was reduced while the histological changes and contractile characteristics similar to that in humans with achalasia were noted. 28,68 One group successfully used this model to study preneoplastic lesions associated with achalasia. 82 BAC has also been successfully applied in the opossum 32,73 and dog.…”
mentioning
confidence: 99%